Desenvolvimento e avaliação biofarmacêutica de supositórios de doxiciclina hiclato para uso veterinário - Christ, Ana Paula (2018)
Veterinary drug therapy can be quite laborious especially when performed in the home environment. Usually the animal drug treatment is done by the oral or injectable route, but the rectal route can be an alternative. The objective of this study was to develop, characterize and evaluate the pharmacokinetics of suppositories containing doxycycline hyclate (DOXH) for veterinary use, aiming to overcome the difficulties of administration and the decrease of adverse effects resulting from administration by other routes. Hydrophilic (S-PEG and SPEG-MET) and lipophilic (S-CBT and S-CBT-BHT) suppositories containing the equivalent of 25 mg doxycycline were developed and the characterization of these formulations was performed by the tests of mean weight, content uniformity, melting point, organoleptic aspects and content. The mean weight and content uniformity (UV method, 350 nm) were evaluated according to the criteria established by the Brazilian Pharmacopoeia. For the determination of the content, a working electrolyte formed by the mixture of solutions A (25 mM sodium carbonate buffer + 5 mM EDTA pH 10.6) and B (acetonitrile) in the ratio 80 : 20, temperature of 24ºC, voltage 25 kV, capillary with 40 cm of effective length and detection at 260 nm. The method presented linearity in the range of 20 to 160 μg / mL, accuracy (DPR <2%), accuracy (recovery of 98 to 102%) and robustness assessed by factorial assay 23. The specificity of the method was confirmed by absence of interference of degradation products from the forced degradation study, as well as methacycline, a common impurity of the doxycycline synthesis process. The stability of the formulations was evaluated over a period of 30 days with the lipophilic formulations with and without antioxidants kept in the refrigerator (5 ± 2 ° C) and the hydrophilic with and without antioxidants kept at room temperature (25 ± 2 ° C). The S-CBT and S-PEG formulations were found to have decreased content during stability (approximately 1 and 12%, respectively) and these formulations were chosen for the pharmacokinetic study. For this study, rabbits weighing 3 to 4 kg were used and the dose of the suppositories was adjusted to 10 mg / kg. The in vivo behavior of doxycycline was evaluated via the IV and rectal routes, using groups with three animals for the pilot study and two other animals for determination of the pharmacokinetic model (n = 5) for each formulation. The pharmacokinetics were evaluated for a 24-hour period by an HPLC method adapted from the literature, and values of half-life close to 8 hours were obtained, Cmax between 1.5 and 2 μg / mL for suppositories, concentrations above MIC for up to 4 hours and 48 and 50% bioavailability for S-PEG and S-MTG, respectively, through noncompartmental analysis (NCA). Through the popPK study it was possible to conclude that the model that best describes the behavior of the drug is that of two compartments. The results obtained provide unpublished data on the rectal absorption of doxycycline and suggest that the formulations developed are promising for use in the veterinary clinic.